Pengembangan Sistem Informasi Event Dan Diskon Dengan Menggunakan Metode V-Shaped - Weiskhy Steven Dharmawan; Ardiyansyah Ardiyansyah (Universitas Asahan, 2022)
Some companies have used information systems as a means of their business, but there are still companies that have not used information systems optimally, one of which is PT Imperium Happy Puppy Pontianak. Happy Puppy Family is a brand that is well known by the public. Happy Puppy Family is a family karaoke business that has been growing for a long time in Indonesia. However, there is some competition that occurs because in one complex there are several karaokes as well, so Happy Puppy must often hold promos and events to attract karaoke consumers at Happy Puppy. Therefore, this study contains research on problem solving PT Imperium Happy Puppy Karaoke by building a programmed information system to organize web-based Event and Discount management using SDLC which contains the Waterfall method by utilizing the CodeIgniter 3 Framework in making the information system website.